Starting an online business and internet marketing 2021 : guide to setting up an e-commerce website, SEO, and digital marketing strategies - S. K. Holder (Independently Published, 2024)
This book is intended for small businesses, start-ups and individual entrepreneurs who want to manage their own online business effectively for Google search engine optimization, to familiarize themselves with common content management system (CMS) features, track their business metrics, and manage their digital marketing and pay-per-click campaigns."